II Coloquio Internacional de Jóvenes Investigadores en Traducción e Interpretación UdeA-UPC - Ramírez Colombier, Marco (2023)
Panelistas: Marco Ramírez Colombier; Heidy Gutierrez; Natalia Silva / Moderan: John Jairo Giraldo Ortiz; Paula Andrea Montoya Arango